Enhanced Seroconversion to West Nile Virus Proteins in Mice by West Nile Kunjin Replicon Virus-like Particles Expressing Glycoproteins from Crimean–Congo Hemorrhagic Fever Virus - Pham-Tue-Hung Tran; Urban Höglund; Olivia Larsson; Sofia Appelberg; Ali Mirazimi; Magnus Johansson; Wessam Melik (Pathogens, 2022)
Removal of genes coding for major parts of capsid (C), premembrane (prM), and envelope (E) proteins on the flavivirus genome aborts the production of infectious virus particles where the remaining genome forms a replicon that retains replicability in host cells. The C-prM-E proteins can also be expressed in trans with the flavivirus replicons to generate single-round infectious replicon virus-like particles (RVPs). In this study, we characterized the use of RVPs based on the Kunjin strain of WNV (WNVKUN) as a putative WNV vaccine candidate. In addition, the WNVKUN C-prM-E genes were substituted with the Crimean–Congo hemorrhagic fever virus (CCHFV) genes encoding the glycoproteins Gn and Gc to generate a WNVKUN replicon expressing the CCHFV proteins. To generate RVPs, the WNVKUN replicon was transfected into a cell line expressing the WNVKUN C-prM-E. Using immunoblotting and immunofluorescence assays, we showed that the replicon can express the CCHFV Gn and Gc proteins and the RVPs can transduce cells to express WNVKUN proteins and the CCHFV Gn and Gc proteins. Our study also revealed that these RVPs have potential as a vaccine platform with low risk of recombination as it infects cells only in one cycle. The immunization of mice with the RVPs resulted in high seroconversion to both WNV E and NS1 but limited seroconversion to CCHFV Gn and Gc proteins. Interestingly, we found that there was enhanced production of WNV E, NS1 antibodies, and neutralizing antibodies by the inclusion of CCHFV Gc and Gn into WNVKUN RVPs. Thus, this study indicates a complementary effect of the CCHFV Gn and Gc proteins on the immunogenicity by WNVKUN RVPs, which may be applied to develop a future vaccine against the WNV.